DETECTION OF ANTIMICROBIAL COMPOUNDS FROM THERMOPHILIC ACTINOMYCETES USING ONE STRAIN MANY COMPOUNDS (OSMAC) APPROACH - Endah Wati Zahroh; Fitria Ningsih; Wellyzar Sjamsuridzal (Universitas Medan Area, 2022)
Actinomycetes are a group of filamentous bacteria with high biosynthetic potential that can produce secondary metabolites. Actinomycetes are known to produce secondary metabolites which are potential as antimicrobial, antitumor, and others. Actinomycetes can be found abundantly in diverse environments, including environments with extremely high temperatures such as hot springs, deserts, geothermal areas, and hydrothermal vents. They can survive in high temperatures due to their membrane lipids containing straight-chains and more saturated fatty acids that protect the membrane's fluidity to maintain membrane function. Thermophilic actinomycetes are potential producers of thermostable enzymes and bioactive compounds, which are important in the pharmaceutical, health, and industrial fields. Thermophilic actinomycetes are still less explored for novel metabolites and antimicrobial compounds due to the difficulty in isolation, maintenance, and preservation in pure culture. Novel bioactive compounds produced by actinomycetes are conventionally discovered by isolating potential strains and screening the compound bioactivity through various bioassays. A sequence-independent approach, termed the OSMAC (one strain many compounds), has been widely used in natural product research for activating cryptic biosynthetic gene clusters (BGCs) by modifying the growth conditions of a bacterial culture. This approach aims to optimize the number of secondary metabolites produced by one single microorganism. The application of the OSMAC method has been proven successful in revealing the biosynthetic potential of bacteria.